The influence of religious coping on family resilience in communicating and solving problems during the COVID-19 pandemic - Bekti Prasetyo, Yoyok; Faridi, Faridi; Masruroh, Nur Lailatul; Melizza, Nur; Hafiz Maulana, Muhammad (Gaceta Médica de Caracas, 2022)
Introduction: Religious coping has a crucial role in overcoming difficult problems in the family. This study aimed to analyze the influence of religious coping on family resilience in communicating and solving problems during the COVID-19 pandemic. Methods: The research design used was descriptive with a cross-sectional survey approach. A total of 242 respondents in East Java Province, Indonesia, were the respondents in this study.